Heritage management: comparing implementation between South Africa and Mexico - Rampete, Obakeng Veronica (My University, 2015)
Heritage management has been a growing phenomenon throughout the world. This growth is due to the increasing necessity to protect the world’s cultural heritage. Heritage management has been closely linked with community participation as well as laws and policies that protect the heritage. Furthermore, site use is also of importance to discover how the heritage is presented, protected and managed. These are the three components that will be the focus of my research. The implementation of heritage management requires a management plan that clearly stipulates and outlines specific procedures to be followed. An ideal management plan includes the components mentioned above, in that it states the stakeholders involved, how the heritage place will be preserved and how the legislation will be used to ensure the protection of such places. This research focuses on rock art sites as the cultural heritage places and the importance of protecting them, with specific focus on rock art sites from South Africa and Mexico. The objective of this study is to analyse the different management plans from sites chosen from the two countries, compare the management plans and recommend a best practice for management plans constructed for rock art sites. The hope is that the recommendations will contribute to managing rock art sites as well as to the International Collaboration formed between South Africa and Mexico.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2015.
Keywords: Heritage tourism--South Africa.; Heritage tourism--Mexico.; Tourism.; Rock paintings.; Art, Prehistoric.